The Relationship Between Parental Involvement With Pain And Anxiety Levels Among Preschool Children During Invasive Procedures - Dior Manta Tambunan; Rustianna Tumanggor (CV. AFDIFAL MAJU BERKAH, 2026)
Hospitalization can be a stressful experience for children, especially when they undergo invasive procedures, which often cause pain and anxiety, which can impact their physical and psychological well-being. This can lead to trauma during hospitalization. This study aimed to identify the relationship between parental involvement and pain and anxiety levels in preschool children during invasive procedures. This study used a quantitative approach and research’s design was a cross-sectional survey. A total of 52 children aged 3-6 years (preschool) with non-oncology cases were treated at the Private Hospital “X” in Medan with purposive sampling. The instruments in this study were questionnaires and pain scale observation. Bivariate test used the non-parametric Spearman's Rho test. The results showed that there was no significant relationship between parental involvement and preschool children's pain level during invasive procedures and there was a significant relationship between parental involvement and anxiety level of preschool children undergoing invasive procedures. Parents' inability to provide appropriate support has the potential to worsen the child's emotional condition, which in turn increases the risk of failure of the procedure, prolongs the duration of the procedure, and adds to the psychological burden on health workers. It is recommended that further researchers conduct intervention studies to identify parental involvement during hospitalization.